Two new species of Gigantochloa (Poaceae: Bambusoideae) from Yunnan, China - Qin, Qiao-Mei; Tong, Yi-Hua; Zeng, Yi; Cai, Zhuo-Yu; Ni, Jing-Bo; Xia, Nian-He (Phytotaxa, 2023)
Two new species of Gigantochloa (Poaceae: Bambusoideae) from Yunnan, China, namely Gigantochloa brachystachya and G. maneensis, are described and illustrated. G. brachystachya is morphologically similar to G. levis, but differs in its infranodal region with a ring of white hairs, culm leaf with erect blade, linear and glabrous auricle being ca. 10 mm wide and less than 1 mm tall, and glabrous ligule being 5–10 mm tall, and foliage leaf with glabrous sheath, 3–5 mm tall ligule and 2–2.5 mm tall outer ligules. Gigantochloa maneensis is morphologically similar to G. callosa, but differs in its intranode and infranodal region both with a ring of white hairs, culm leaf with densely black-hispid sheath abaxially and without stripes, erect blade and oblong auricle being 6–7 mm wide, and sparsely brown-hispid foliage leaf sheaths.